Eu conspirei com poetas e fingi ser um deles: a experiência poética de E. P. Thompson - Agrela, Raul Victor Vieira Ávila de (2019)
The exercise this research offers is to read historicaly the poems of english written E. P. Thompson reunied at Cllected Poems (1999). The objetice is examine the Thompson’s poetic experience, interrogating your poetic literature and all questions that his poems make it possible, as the development of ideia that human agency in history at Thompson’ thought, thoughout poems written at 1940’s. Another point is show Thompson read the writter William Morris and dialogue with other writters, like Auden and Orwell, to answer the questions that appears explicity in poems written at 1950’s (In Praise of Hangmen and Homege to Tibor Dery). At third moment, the research trates the relations of Thompson with marxism and history though of two poems written in 1973 (Homage to Salvador Hallende and My Study) to understand his tematic esquece of poems about Christmas, Infant and Emperor, whereby will present his resistance and rebel’s points in front of apocalitic turning of arms running.